Neo-Thomism in action : law and society reshaped by neo-scholastic philosophy, 1880-1960 - Decock, Wim, 1983-; Raymaekers, Bart; Heyrman, Peter (Leuven : Leuven University Press, 2021)
In his encyclical 'Aeterni Patris' (1879), Pope Leo XIII expressed the conviction that the renewed study of the philosophical legacy of Saint Thomas Aquinas would help Catholics to engage in a dialogue with secular modernity while maintaining respect for Church doctrine and tradition. As a result, the neo-scholastic framework dominated Catholic intellectual production for nearly a century thereafter.0This volume assesses the societal impact of the Thomist revival movement, with particular attention to the juridical dimension of this epistemic community. Contributions from different disciplinary backgrounds offer a multifaceted and in-depth analysis of many different networks and protagonists of the neo-scholastic movement, its institutions and periodicals, and its conceptual frameworks. Although special attention is paid to the Leuven Institute of Philosophy and Faculty of Law, the volume also discloses the neo-Thomist revival in other national and transnational contexts. By highlighting diverse aspects of its societal and legal impact, 'Neo-Thomism in Action' argues that neo-scholasticism was neither a sterile intellectual exercise nor a monolithic movement. The book expands our understanding of how Catholic intellectual discourse communities were constructed and how they pervaded law and society during the late 19th century and the first half of the 20th century.
Neo-Thomism, law and society : a prolegomenon to further study / Wim Decock -- The Landscape of Neo-Thomism -- Religious, political and social settings of the revival of Thomism, 1870-1960 / Emiel Lamberts -- The 1920s Fracophone Thomistic revival / Philippe Chenaux -- Neo-Thomism at Leuven's Faculty of Law -- Joeri De Smet -- National Contexts and International Networks -- Vetera novis augere, or, Leuven Quebec augere : Lionel Groulx, Neo-Thomism and French-Canadian nationalism / Kasper Swerts -- Reception and adaptation of Neo-Thomism in East-Central Europe, between the intellectual and social involvement of the Catholic Church / Jakub Štofaník -- The influence of Neo-Thomism on Catholic social policy-making in Belgium, 1880-1914 / Jo Deferme -- Between Gospel and constitution : neo-scholastic traces in the legal world of nineteenth-century Spain / Faustino Martínez Martínez -- The notion of war in the Rivista di Filosofia Neo-Scolastica, 1914-1918 / Cinzia Sulas -- Protagonists -- A conservative reading of Rerum Novarum through a neo-scholastic lens : the Jesuit Augustin Castelein (1840-1922) and the Belgian Patrons Catholiques / Peter Heyrman -- Aruthur Vermeersch on colonial and conjugal morality : a presentist approach to Saint Thomas / Vincent Genin -- Joannes Aengenent (1873-1935) : a Thomistic sociologist's call for a more humane economy / Erik Sengers -- Antoine Pottier and the Neo-Thomistic roots of social justice / Jean-Pierre Delville -- Neo-Thomism and the debates on the just wage in Belgium (1879-1914) / Kwinten Dewaele.
Included bibliographical references and index.
Online resource; title from digital title page (viewed on January 20, 2022).
JSTOR
Keywords: Neo-Scholasticism.; Thomism; Néo-scolastique.; Thomisme; Thomism; Neo-Scholasticism